Modern approaches to cervical cancer screening (a review) - M. I. Pavliuchenko; Yu. Ya. Krut; V. H. Siusiuka; O. V. Deinichenko (Patologìâ)
The aim – systematization of data from modern scientific sources and own knowledge and experience regarding the problems, advantages and prospects of the development of various methods of diagnosing pathological conditions of the cervix.